2003
DOI: 10.1063/1.1575935
|View full text |Cite
|
Sign up to set email alerts
|

Structural and optical properties of epitaxial BaTiO3 thin films grown on GdScO3(110)

Abstract: We have prepared 1-m-thick epitaxial BaTiO 3 thin films on GdScO 3 (110) using pulsed laser deposition. The structural perfection of the films was revealed by a rocking curve width of ⌬ϭ0.13°for the 002 BaTiO 3 reflection and a Rutherford backscattering spectrometry/channeling minimum yield, min , of 0.5% measured for the Ba signal behind the surface peak. High-resolution transmission electron microscopy revealed an epitaxial relationship between BaTiO 3 and GdScO 3 and a sharp interface between the substrate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
52
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(53 citation statements)
references
References 14 publications
1
52
0
Order By: Relevance
“…In the PbTiO 3 / MgO system, depending on cooling rate from the growth temperature to room temperature, a bilayer structure of a-domain PbTiO 3 films near the MgO substrate and c-domain PbTiO 3 films near the free surface was reported [11]. In epitaxial BaTiO 3 films the c-domain films were frequently observed on various substrates using different deposition techniques [1,[12][13][14][15]. Recently, it was reported that orientations of epitaxial BaTiO 3 thin films on SrTiO 3 can be controlled by adjusting the parameters of the deposition process [16].…”
Section: Introductionmentioning
confidence: 99%
“…In the PbTiO 3 / MgO system, depending on cooling rate from the growth temperature to room temperature, a bilayer structure of a-domain PbTiO 3 films near the MgO substrate and c-domain PbTiO 3 films near the free surface was reported [11]. In epitaxial BaTiO 3 films the c-domain films were frequently observed on various substrates using different deposition techniques [1,[12][13][14][15]. Recently, it was reported that orientations of epitaxial BaTiO 3 thin films on SrTiO 3 can be controlled by adjusting the parameters of the deposition process [16].…”
Section: Introductionmentioning
confidence: 99%
“…First, we use the fact that on the (110) O surface the DSO lattice is extremely closely matched to that of SRO. [13] Further, the small structural anisotropy in DSO is used to pin the structure of the SRO layer COMMUNICATIONS …”
mentioning
confidence: 99%
“…Rare-earth scandate (REScO 3 ) substrates have been recently developed with the larger lattice constants of ferroelectric and multiferroic perovskites in mind. [280][281][282][283][284] In addition to appropriate substrate single crystals, a method to prepare substrates with a specific chemical termination of the surface is a prerequisite for atomic-layer-controlled thin film growth of epitaxial heterostructures. For example, chemical-mechanically polished (001) SrTiO 3 substrates display a mixture of SrO and TiO 2 terminated surfaces.…”
Section: Integration Of Oxides (1) Substrates and Substrate Prepamentioning
confidence: 99%